Stem cells, tissue engineering and regenerative medicine - Warburton, David (Singapore : World Scientific, 2015)
Stem cells, tissue engineering and regenerative medicine are fast moving fields with vastly transformative implications for the future of health care and capital markets. This book will show the state of the art in the translational fields of stem cell biology, tissue engineering and regenerative medicine. The state of developments in specific organ systems, where novel solutions to organ failure are badly needed such as the lungs, kidney and so forth, are discussed in various chapters. These present and future advances are placed in the context of the overall field, offering a comprehensive and quick up-to-date drink from the fountain of knowledge in this rapidly emerging field. This book provides an investigator-level overview of the current field accessible to the educated scientific generalist as well as a college educated readership, undergraduates and science writers, educators and professionals of all kinds.
Keywords: Stem cells; Tissue Engineering; Regenerative medicine